Does regionalism beget regionalism? The relationship between norms and regional partnerships for economic development - Olberding, Julie Cencula (2002)
Social scientists traditionally have described local governments as competing with each other for residents and businesses. But in a number of metropolitan areas in the United States, local governmental officials have formed groups voluntarily to enhance the economic development of multijurisdictional areas. This article develops a theory that asserts the key determinants of the formation of these regional partnerships for economic development are cooperative norms-or a tradition of regional cooperation-and need. The theory also posits that norms influence regional partnerships' organizational structure and processes. Hypotheses are tested empirically using data from all metropolitan areas in the United States and responses to a national survey of regional partnerships for economic development. Results provide some support for the theory that norms and need are both positively related to the formation of regional partnerships for economic development. Support is weak that norms are related to the organizational characteristic of regional partnerships for economic development. - Reproduced.
Keywords: Economic and social development - United States; Regionalism; Economic and social development - United States; Economic and social development